Proposed Attack Strategy For Ermi Tours In Order To Expand To The New Market - Martadinata, Indriana Qoriaini; Toha, Mohammad (The Indonesian Journal of Business Administration, 2014)
Abstract – Ermi Tours is a local company for tour and travel business in Indonesia, which provide the best quality with affordable price in tour and travel services for both international and domestic travelers. The business issues faced by Ermi Tours is no growth in its sales because of the tight competitive on the limited market. Whereas, the fact states that the potential market in the tourism industry is growing rapidly. Ermi Tours planned to expand the business to the new market to solve the issue so they need to explore the current business to formulate an appropriate attack strategy. The current business explored with the external and internal environment analysis to identify existing that strengths, weaknesses opportunities and threats possessed by Ermi Tours, called SWOT analysis. Grand Strategy also performed to ensure that expand the business is the most appropriate strategy to execute. The formulation of attack strategy and its steps are determined through five key elements of Strategy Diamond, which also involves Strategic Moves and Competitor Analysis while selecting the most appropriate attack strategy to compete the new market. All things considered, this tourism industry has an attractive market and has promising growth while expanding to the new market. However, to penetrate new market and win the competition, Ermi Tours must take appropriate implementations adapted to its capability to improve performance and competitive position of the company in order to capture market opportunities and greater profits.Keywords: business strategy, attack strategy, tour and travel business, strategy diamond